Community Well–being Development through Community Context–based Applications : A Case Study of the Thai Songdam Dance in Ban Don Thong, Don Khoi, Kamphaeng Saen, Nakhon Pathom - Nilkote, Reongwit; Charoenlak, Nipawan; et al. (Journal of Cultural Approach, 2022)
This research was a qualitative. The objective was to develop learning guidelines for community well-being through context-based applications. The research area was Ban Don Thong, Kamphaeng Saen, in Nakhon Pathom. The Duncan group and community leaders were key participants in this research. Key processes and procedures included: (1) community preparedness; (2) social capital assessment; (3) taking lessons learned and knowledge management about the community situation and project implementation in the community; (4) synthesizing the factors affecting the implementation of community well-being development through context-based applications; (5) returning data to the community; and (6) summarizing and presenting the guidelines for community well-being development through context-base applications. The results show that the development of community well-being through context-based applications included five main activities: searching for the community’s social and cultural capital; developing activities based on the community’s society and culture; meeting and empowering groups; activities to promote physical health; and activities to transmit traditions and culture. The factors affecting the development of community well-being were composed of five factors: common perception, mutual interests and benefits, stakeholder participation, interaction and knowledge management, and use of community context and social capital. In summary, the learning guidelines for developing community well-being must be implemented through context-based applications; using social capital, volunteer leadership, network partner support and collaboration, community participatory management, and community well-being activities.